Aging Perception in Older Adults - Leila Sadegh Moghadam; Mahshid Foroughan; Farahnaz Mohammadi; Fazlollah Ahmadi; Akram Farhadi; Shima Nazari; Nargeskhaton Sadeghi (Sālmand, 2016)
Objectives: Perception of ageing has been introduced as an independent predictor of functional disability and mortality in older adults. The present study aimed to investigate the perception of aging in the literature and reach a more comprehensive understanding of this concept. Methods & Materials: A comprehensive search of electronic databases of ProQuest, Web of Science, CINAHL, Scopus, PubMed, ScienceDirect, ISC, Irandoc, Magiran, and Iranmedex was conducted using the English and equivalent Persian keywords of “Aging Perception”, “Meaning of Aging”, “Experience of aging”, with no time limitation. Results: Perception of aging refers to how older people feel about their aging in their socio-cultural context. It comprises all aspects of the awareness, perception, experience, evaluation, interpretation, and identification of own aging process. Factors which can affect the perception of aging can be divided into 2 groups: Personal factors (attitudes, subjective age, health status, economic status, material status, religion, knowledge about aging, satisfaction with aging, extent of believing in internal control compared to external one) and social factors (age discrimination, modernity, social and family relationships). Accurate measurement of aging perception can be used as a good indicator of predicting person’s future health status, determining his or her life satisfaction, and adaptation to life changes in this period. Conclusion: The context-based concept of aging perception in older people could be a good predictor of health status, determining factor of life satisfaction, and adaptability to changes in old age. Further investigation is recommended in this topic.